Knockdown of NEK7 alleviates anterior cruciate ligament transection osteoarthritis (ACLT)-induced knee osteoarthritis in mice via inhibiting NLRP3 activation - Wei Sun; Maoxing Yue; Guangmin Xi; Kai Wang; Jiaming Sai (Taylor & Francis Group, 2022)
Osteoarthritis is thought to be a NLRP3-related disease. NEK7 is an essential mediator for NLRP3 inflammasome activation. This study aimed to demonstrate whether NEK7 has regulatory roles in the pathogenesis of osteoarthritis. C57BL/6 mice were subjected to anterior cruciate ligament transection osteoarthritis (ACLT) for constructing animal models of osteoarthritis. Injection of adeno-associated virus (AAV) expressing NEK7-specific shRNA into the knee joints of mice, following of which immunohistochemistry, qRT-PCR, western blotting, Safranin-O Fast Green staining, ELISA, and co-immunoprecipitation were performed to determine the effects of NEK7. NEK7 was highly expressed in the joint tissues of ACLT mice. As compared with shScr, AAV delivery of NEK7 shRNA significantly inhibited cartilage degeneration, OARSI score, and serum CTX-II and COMP levels. AAV delivery of NEK7 shRNA downregulated the expression of matrix-degrading enzymes (ADAMTS-4, MMP3, and MMP13) and upregulated the expression of ECM-related molecules (SOX9, collagen II, and aggrecan). In addition, AAV delivery of NEK7 shRNA alleviated ACLT-induced synovial inflammation, as was evidenced by the decreased levels of TNF-α, IL-6, IL-1β, and IL-18 and increased levels of IL-10. In the joint tissues of ACLT mice, NEK7 interacted with NLRP3 proteins. AAV delivery of NEK7 shRNA inhibited the protein interaction, and thereby inhibited the activation of the NLRP3 inflammasome. AAV delivery of NEK7 shRNA has no significant effects on cartilage degeneration and synovial inflammation in Nlrp3−/− mice. In conclusion, knockdown of NEK7 exerted anti-osteoarthritic effects, possibly via inhibiting the activation of the NLRP3 inflammasome. This study provided a novel mechanism of NEK7-NLRP3 interaction affecting osteoarthritis.